Vulnerability and resilience to natural hazards - Fuchs, Sven; Thaler, Thomas (Cambridge University Press, 2018)
"In recent years there has been growing recognition that disaster risk cannot be reduced by focusing solely on physical hazards without considering factors that influence socio-economic impact. Vulnerability: the susceptibility to the damaging impacts of hazards, and resilience: the ability to recover, have become popular concepts in natural hazard and risk management. This book provides a comprehensive overview of the concepts of vulnerability and resilience and their application to natural hazards research. With contributions from both physical and social scientists it provides an interdisciplinary discussion of the different types of vulnerability and resilience, the links between them, and concludes with the remaining challenges and future directions of the field. Examining global case studies from the US coast to Austria, this is a valuable reference for researchers and graduate students working in natural hazard and risk reduction from both the natural and social sciences"--